ASSOCIATION OF POLYMORPHISM IN TICAM1 GENE WITH PROTECTION TO MODERATE/SEVERE COVID-19 - Braga, Matheus; E. Santiago Silva, Pedro; H. U. Yamanaka, Aléia; H. Souza, Victor; Grava, Sergio; F. Sela, Ana; S. F. Neves, Janisleya; Zacarias, Joana; Jeane Eliete Laguila Visentainer, Jeane (Arquivos do Mudi, 2023)
Clinical outcomes of Covid-19 have shown variability between individuals and populations. TICAM1 gene encodes the TRIFF protein, essential in the antiviral response, then the purpose of the study was to assess the effect of the polymorphism (rs2292151) G>A of TICAM1 gene on the severity of COVID-19 in individuals from the northern region of Paraná. A case-control study was performed, including patients, 100 mild and 50 moderate/severe Covid-19 cases, classified according to the WHO, by Hospital Paraná, Maringá, Brazil. The exclusion criteria used were: patients with heart disease, liver disease, other respiratory diseases, HIV, and cancer. The (rs2292151) G>A polymorphism was genotyped by qPCR and statistical analysis was performed using logistic regression in the SNPStats software. The genotype distribution was according to the expected in the Hardy-Weinberg equilibrium. There was an association between the A/A genotype in a codominant model with protection against the severity of the disease (OR=0.14, 95% CI 0.03.-0.75, P = 0.01). The frequency of genotype A/A was 12% in mild cases and 4% in serious cases; the G/A was 44% in mild cases and 30% in serious cases, and the G/G was 44% in mild cases and 66% in serious cases. We can conclude that the A/A genotype (in a codominant genetic model) of the polymorphism (rs2292151) G>A was associated with a protection factor for moderate/severe Covid-19 in this population, however, the genotype determination should be done in a high number of patients.